2013
DOI: 10.1074/jbc.m112.429886
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Type III Polyketide Synthase Involved in Quinolone Alkaloid Biosynthesis from Aegle marmelos Correa

Abstract: Background: Type III polyketide synthase is hypothesized to produce quinolones, but no such enzyme has been identified so far. Results: QNS, a type III PKS from Aegle marmelos synthesizes diketide 4-hydroxy-1-methyl-2H-quinolone using a unique substrate binding site. Conclusion: QNS is a novel 4-hydroxy-1-methyl-2H-quinolone synthase. Significance: This is the first report of a gene involved in quinolone biosynthesis from plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 39 publications
3
44
1
Order By: Relevance
“…Type III PKSs are promiscuous enzymes that have a broad tolerance for diverse substrates and are able to catalyze multiple reactions [84,85]. Type III PKSs that use cyclic nitrogen-containing substrates have been previously characterized for their roles in alkaloid production [86][87][88]. However, unlike these previous studies the predicted substrate in TA metabolism, N-methyl-∆ 1 -pyrrolinium cation (19) [81].…”
Section: Tropane Alkaloid Biosynthesiscontrasting
confidence: 43%
“…Type III PKSs are promiscuous enzymes that have a broad tolerance for diverse substrates and are able to catalyze multiple reactions [84,85]. Type III PKSs that use cyclic nitrogen-containing substrates have been previously characterized for their roles in alkaloid production [86][87][88]. However, unlike these previous studies the predicted substrate in TA metabolism, N-methyl-∆ 1 -pyrrolinium cation (19) [81].…”
Section: Tropane Alkaloid Biosynthesiscontrasting
confidence: 43%
“…Site-directed mutagenesis studies showed that a triple ACS mutant (S132T/A133S/V265F) was transformed into a functional CHS with some ACS side activity. Intriguingly, a similar triple QNS mutant (S132T/A133S/V265F) had no activity, but a double QNS mutant (S132T/A133S) was converted into a functional CHS that utilized p-coumaroyl-CoA instead of N-methylanthraniloyl-CoA, and the number of elongation steps was increased, leading to the production of naringenin [57]. This suggests slight differences in the active site architectures of ACS and QNS.…”
Section: Acridone Synthase and Quinolone Synthasementioning
confidence: 96%
“…Homology modeling revealed that the CoA-binding tunnel, the Cys-His-Asn catalytic triad, and most of the active site residues are maintained in A. marmelos QNS. However, the CHS-conserved residues Thr132, Ser133, and Phe265 are replaced by Ser132, Ala133, and Val265, respectively [57]. These substitutions are also present in R. graveolens ACS, hence, they are likely to play an important role in starter unit specificity [58].…”
Section: Acridone Synthase and Quinolone Synthasementioning
confidence: 99%
“…The other type III PKS is the recently reported quinolone synthase (QNS) from Aegle marmelos, which produces the diketide 4-hydroxy-N-methylquinolone by the one-step condensation of N-methylanthraniloyl-CoA with one molecule of malonylCoA (Fig. 1A) (12). The two type III PKS enzymes thus catalyze the C-N bond-forming reactions, in addition to the C-C bond formation, to generate the anthranilate-derived alkaloid scaffolds.…”
mentioning
confidence: 99%